(untitled) (Web of Teachers: Inderscience Research, 2025)
This study examines the integration of artificial intelligence tools into the process of teaching the English language in secondary schools of Uzbekistan. It discusses the main advantages of using artificial intelligence technologies, such as individual learning, interactive communication, and effective assessment methods. At the same time, it identifies the main challenges faced by teachers and students, including the lack of digital knowledge, limited technical resources, and difficulties in adaptation. The study provides several recommendations for improving the quality of English language education through the use of artificial intelligence tools.